Políticas públicas para o setor de transportes rodoviários na perspectiva dos caminhoneiros autônomos: uma análise a partir da matriz de posicionamento - Stachio, Larissa Paula (2022)
The main objective of this dissertation was to verify how the policies related to road cargo transport are applied to autonomous truckers from the process of economic opening in Brazil in 1990. The research was based on a qualitative analysis, using systematic bibliographic research, aiming at a historical narrative about the entire process of adoption of road cargo transport as the main modal and the search for public policies that were related to autonomous truckers. Strings were applied for research seeking articles and scientific papers, these using the capes journal portal, and non-academic publications, these using sites such as Fundação Getúlio Vargas, National Transport Confederation and National Land Transport Agency. With the selection of the materials to be used in the research, the Atlas.ti software was used to select the relevant excerpts in each document and for the classification based on the search strings. After selecting these citations, the positioning matrices were set up based on the method presented by Laurence Bardin in her book Content Analysis (2016). Among the results obtained, considering the analysis of public policies Concession of Federal Highways, Reduction of the Tax on Industrialized Products, Trucker's Law, Freight Tableing and Giant Asphalt Program, it was obtained that only the public policy related to freight tableing becomes beneficial to autonomous truckers. As a result, it was also verified that there are no scientific studies related to autonomous truckers and the theme of economics, by which it was suggested that further studies be carried out.